Synthesis and characterization of a molecularly imprinted polymer for Pb2+ uptake using 2-vinylpyridine as the complexing monomer - Yusof, Nor Azah; Beyan, Appri; Haron, Md. Jelas; Ibrahim, Nor Azowa (Penerbit UKM, 2010)
Molecularly imprinted polymer (MIP) particles for selective extraction of Pb2+ from aqueous media were prepared using non-covalent molecular imprinting methods. 2-vinylpyridine was chosen as the complexing monomer. The imprinted polymer was synthesised by radical polymerisation. The template (Pb2+) was removed by leaching with 0.1 M HCl. The polymer particles (imprinted and non-imprinted) were characterised by IR spectroscopy. The effect of different parameters such as pH, kinetic, adsorption isotherm and selectivity were evaluated. The maximum adsorption capacity is 150 μg Pb2+/mg MIP. The adsorption efficiently occurred at pH 6. The selectivity coefficients of the imprinted polymer particles for Pb2+/Zn2+ and Pb2+/Al3+ were 13.55 and 1.71, respectively.